Institute of Metals Division - The Effect of Ferrite on the Mechanical Properties of a Precipitation-Hardening Stainless Steel - Vito J. Colangelo (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
The primary object of this study was to determine the effect of ferrite and its orientation upon the mechanical properties of a precipitation -hardening stainless steel with particular attention to the short-transverse properties. The investigation consisted of Jour major parts : the preliminary investigation of billet properties, the effect of forging reduction and ferrite content upon mechanical properties, the effect of notch orientation upon impact strength, and the relationship of heat composition to ferrite content. Low ductility and impact strength in the short transverse direction were found to he associated with the orientation and shape of- the ferrite plates. It was also determined that impact strength varied with notch orientation. The test values obtained with the notch perpendicular to the plane of the ferrite plate were lower than those obtained in the notch-parallel condition. The over-all investigation showed that high ferrite contents in general had a deleterious effect upon mechanical properties and that the ferrite content could he minimized by exercising rigorous control of the heat composition. A careful balance of elements, nitrogen in particular, must he maintained in order to reduce the formation of ferrite. THE precipitation-hardening stainless steels were developed to fulfill a need for high-strength corrosion-resistant alloys. In the annealed condition they are soft and ductile and possess many of the desirable characteristics of the austenitic stainless steels. In the hardened condition, the alloys exhibit the high strength and hardness of the martensitic stainless steels. The alloy under consideration in this investigation has a nominal composition as follows: C Mn Si Cr Ni Mo N 0.13 0.95 0.25 15.50 4.30 2.75 0.10 The hardening mechanism is identical to that of other hardenable steels in that it depends upon the transformation of austenite to martensite. This alloy because of its annealed structure and its ability to be hardened combines the desirable forming and corrosion properties of the austenitic grades with the high hardness and strength levels attainable with the hardenable grades. The reason for this apparent duplicity of proper- ties can be explained by considering a basic metallurgical difference between the hardenable stainless steels and those of the austenitic group. Both types are austenitic at 1800°F but, while the martensitic grades transform to martensite upon rapid cooling to room temperature, the austenitic grades remain austenitic even when cooled to temperatures below room temperature. The major difference then is in the degree of austenite stability. This stability can quantitatively be described by the Ms temperature. The Ms is defined as that temperature at which austenite begins to transform to martensite. The austenitic grades for example may be cooled to -300°F without producing significant quantities of martensite. The hardenable stainless steels on the other hand have an Ms temperature in the vicinity of 400" to 700°F. In cooling to room temperature, these alloys traverse the entire Ms-Mf range and show almost complete transformation to martensite. The semiaustenitic stainless steel, however, occupies an intermediate position with respect to its austenite stability. The analysis is so balanced that the Ills temperature lies at or slightly above room temperature. The resulting alloy retains much of its austenite at room temperature and yet responds to hardening heat treatments. Achieving this delicate balance of elements is therefore of great importance. Slight imbalances of the equivalent Cr-Ni ratios frequently result in the presence of 6 ferrite. It is the effects of this ferrit with which we are concerned, more specifically the effect of the quantity and ferrite orientation upon mechanical properties, particularly ductility. PROCEDURE A) Preliminary Investigation of Billet and Forging Properties. In order to determine the effect of ferrite on billet properties, billet stock from three heats with various ferrite contents was utilized. Tensile specimens were obtained in the transverse and longitudinal directions from this material and heat-treated as shown in Tables I and 11. Forgings were made from these same heats, the purpose being to determine what effect, if any, the ferrite might have upon the mechanical properties. These forgings were made in such a manner as to elongate the ferrite in the longitudinal and transverse directions. The method of forging was as follows. A section was cut from a 6-in.-sq billet of Heat A and flat-forged to 1-1/2 in. thick. Working was done from one direction only with no edging passes as shown